Self-assembling and piezofluorochromic properties of tert-butylcarbazole-based Schiff bases and the difluoroboron complex. (January 2017) - Sun, Jiabao; Sun, Jingbo; Mi, Wenhua; Xue, Pengchong; Zhao, Jinyu; Zhai, Lu; Lu, Ran
Abstract: New tert -butylcarbazole-based Schiff basesTPMP andTPMA, as well as the difluoroboron complex of salicylaldimineTPOB were synthesized. It was found thatTPMP andTPMA without any traditional gelation group could form organogels in toluene and o -dichlorobenzene, etc., stimulated by ultrasound. It was suggested that the planar π-skeletons and the large steric effect of tert -butyl groups would lead to appropriate π-π interaction to induce the gel formation. Interestingly, the nanofibers formed from salicylaldimine derivativeTPMP could emit strong yellowish green light under UV irradiation. It should be noted that the difluoroboron complex ofTPOB with non-planar aromatic unit could not gelate the selected solvents on account of the weak π-π interaction. However, it showed reversible piezofluorochromism. The as-prepared crystal ofTPOB emitted strong yellow light and could be transformed into the powders emitting orange red light after grinding, and the fluorescence could recover when the ground powders were heated. Such reversible changes of the emitting colors forTPOB by the treatment of grinding and heating was resulted from the transformation between crystalline and amorphous states. Herein, we provided the strategy for fabricating new nontraditional π-gels directed by appropriate π-π interaction and new piezofluorochromic dyes via the introduction of non-planar π-skeletons. Graphical abstract: Highlights: tert -Butylcarbazole-based Schiff bases and difluoroboron complex were synthesized. TPMP andTPMA without any tradition gelation group could form organogels. Appropriate π-π interaction between π-skeleton with tert -butyl leads to the gelation. TPOB showed reversible piezofluorochromism.